Microbial Infections in Patients Suffering from Burn Injuries: A Systematic Review (Medicine Today, 2025)
Polymicrobial infections are common in patients suffering from burn injuries. Hospitalized patients are at a heightened risk of contracting hospital-acquired infections and extended hospital stays raise the possibility of infection with resistant organisms. Pseudomonas aeruginosa, Proteus mirabilis, Acinetobacter baumannii, and Klebsiella pneumoniae are the most often found multidrug-resistant (MDR) Gram-negative bacteria in burn wound infections (BWIs). BWIs caused by Gram positive organism like Staphylococcus and Streptococcus are also prevalent. Fungi-like Candida species appear to occur also. Nonetheless, opportunistic pathogen infection is highly prevalent in burn victims. Variations in geographic location and infection control practices result in variations in the causal agents of BWIs. All things considered, increased serum cytokine levels, systemic immune response and immunosuppression are indicative of burn injuries. Therefore, prompt identification and intervention can quicken the healing of wounds and lower the chance of developing new infections at the site of injury. A multidisciplinary approach from infectious disease experts and burn surgeons is also required to effectively track antibiotic resistance in BWI pathogens, prevent the super-spread of MDR infections and enhance treatment results.Medicine Today 2025, Vol.37 (2): 263-268